The Relationship of Olecranon Apophyseal Ossification and Sanders Hand Scores with the Timing of Peak Height Velocity in Adolescents. (18th August 2021) - Greene, Janelle D.; Yu, Kristin; Li, Don T.; Furdock, Ryan J.; Li, Eric; Liu, Raymond W.; Cooperman, Daniel R.
Abstract : Background: The onset of peak height velocity (PHV) guides the timing of interventions in the growing child. The purpose of the present study was to validate the Diméglio olecranon grading system and to compare these scores with the Risser/triradiate closure (TRC), proximal humerus, and Sanders hand scores. Methods: Eighty children with annual serial radiographs were selected from the Bolton-Brush collection. The olecranon apophysis was graded with use of lateral radiographs of the elbow. The mean age to PHV was determined for each stage, and reliability was calculated with use of an intraclass correlation coefficient (ICC). Olecranon stage was combined with age, sex, and height in a generalized estimating equation (GEE) model to predict PHV. Predictive performance of this model was evaluated with use of tenfold cross-validation such that the model was trained on 90% of the radiographs and was asked to predict the PHV of the remaining 10%. Results: PHV is closely associated with olecranon stage, with stage 1 occurring 3.0 years before PHV and stage 7 occurring 3.4 years after PHV. Stage 5 was found to occur at PHV. Scoring system reliability was high across an array of observers (ICC = 0.85 ± 0.07). The GEE model showed that this olecranon system outperforms the Risser/TRC system in predicting PHV and is comparable with the humerus and Sanders hand systems. When combined with age and sex, the olecranon system successfully predicted PHV such that 62% of PHV predictions were accurate within 6 months and 90% of PHV predictions were accurate within a year. Conclusions: Our data show that stage 5 occurs at PHV, contrary to previously published data. When combined with age and sex, the olecranon system successfully predicts PHV within a year in 90% of cases, establishing a single lateral view of the olecranon as a simple alternative to more complex grading systems. Last, we describe novel 3 variations in olecranon morphology and provide a guide for accurate olecranon staging. Clinical Relevance: Understanding PHV is critical in the treatment of many pediatric orthopaedic disorders. The revised olecranon staging system will allow for more accurate determination of this variable.